Usability Evaluation on “LYFY” as an e-Marketplace Tool for the National Batik Industry - Witanto, Elizabeth Nathania; Permana, Belinda Putri Adi; Wiradinata, Trianggoro; Oktian, Yustus Eko; Maryati, Indra (Universitas Multi Data Palembang, 2025)
In the current digital era, e-commerce has emerged as a primary choice for many business actors, particularly Micro, Small, and Medium Enterprises (MSMEs) specializing in batik products. Live streaming commerce has gained popularity as an effective marketing strategy, enabling direct interaction between sellers and consumers. However, challenges such as audience engagement and the need for prompt responses to questions or comments during live sessions pose significant issues that need to be addressed. To assist MSMEs optimize this strategy, the application of Artificial Intelligence (AI) and Machine Learning (ML) technologies can provide innovative solutions. LYFY, an AI-driven e-marketplace platform, was developed to support batik MSMEs by facilitating product promotion, enhancing consumer interaction, and enabling efficient transactions through features such as live streaming and size prediction tools. To assess the effectiveness of LYFY's user interface and overall experience, a usability evaluation was conducted using two standardized frameworks: ISO 9241-11 and the Usability Metric for User Experience (UMUX-Lite). The finding suggests that LYFY provides a high-quality user experience and is well-positioned to support the digital transformation of Indonesia’s batik SMEs.